Anti-Vivisection and the Profession of Medicine in Britain A Social History - Bates, A.W.H (The Palgrave Macmillan Animal Ethics Series, 2017)
This book is open access under a CC BY 4.0 license. This book explores the social history of the anti-vivisection movement in Britain from its nineteenth-century beginnings until the 1960s. It discusses the ethical principles that inspired the movement and the socio-political background that explains its rise and fall. Opposition to vivisection began when medical practitioners complained it was contrary to the compassionate ethos of their profession. Christian anti-cruelty organizations took up the cause out of concern that callousness among the professional classes would have a demoralizing effect on the rest of society. As the nineteenth century drew to a close, the influence of transcendentalism, Eastern religions and the spiritual revival led new age social reformers to champion a more holistic approach to science, and dismiss reliance on vivisection as a materialistic oversimplification. In response, scientists claimed it was necessary to remain objective and unemotional in order to perform the experiments necessary for medical progress.